SOSIALISASI GUNA PENINGKATAN KESADARAN MASYARAKAT TERHADAP DAMPAK JUDI ONLINE DAN TEKNOLOGI YANG DIGUNAKAN - Aulia Ikhsan; Iis Aisyah; Cendra Harmon (Abdi Jurnal Publikasi, 2025)
The development of digital technology brings many benefits; however, it also presents serious challenges, one of which is the increasing access and involvement of adolescents in online gambling practices. Online gambling often disguises itself in the form of games or applications that appear harmless, making students vulnerable to being trapped without realizing it. Therefore, digital education and literacy are essential to be introduced from an early stage, particularly in secondary education environments. The Community Service Program (PKM) carried out by lecturers and students of Universitas Pamulang aims to raise awareness and enhance the understanding of students at SMK Bintang Nusantara regarding the dangers of online gambling and the technology behind it. The socialization activities were conducted through interactive seminars, discussions, educational video screenings, and real case studies. In addition to delivering information about the psychological, social, and academic consequences, the program also equipped students with technical knowledge about technological methods such as VPNs, masking applications, and illegal websites. The results of the program showed an increase in students’ understanding of the risks of irresponsible internet use, as well as greater active participation during question-and-answer sessions. Support from the school, teachers, and parents also became an important indicator of the program’s success. It is expected that similar activities can be carried out sustainably and integrated as part of the school’s digital literacy program.